2021
DOI: 10.1002/ece3.8269
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation and regulatory variation in acetylcholinesterase genes contribute to insecticide resistance in different populations of Leptinotarsa decemlineata

Abstract: Resistance to insecticides is a serious global problem that can negatively affect human health, food production, and agriculture (Gould et al., 2018). Since 1914, up to 597 arthropod species have become resistant to more than 300 insecticides (Roush & Tabashnik, 2012;Sparks & Nauen, 2015). The evolution of insecticide resistance is a process of genetically based decrease in population susceptibility to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…The above-mentioned study has concluded that in the propoxur-resistant strain, there was a decrease in the affinity of the enzyme to the insecticides and substrate, as well as a decrease in the catalytic efficiency of AChE against the specific substrate (ATC). Similar results were obtained in other studies where authors investigated AChE in OPs- and carbamate-resistant insects [ 58 , 59 , 60 ]. A simultaneous decrease in the Vmax and Km are usually effects of an uncompetitive inhibitor due to the changes in the enzyme-substrate complex equilibrium [ 61 ].…”
Section: Discussionsupporting
confidence: 90%
“…The above-mentioned study has concluded that in the propoxur-resistant strain, there was a decrease in the affinity of the enzyme to the insecticides and substrate, as well as a decrease in the catalytic efficiency of AChE against the specific substrate (ATC). Similar results were obtained in other studies where authors investigated AChE in OPs- and carbamate-resistant insects [ 58 , 59 , 60 ]. A simultaneous decrease in the Vmax and Km are usually effects of an uncompetitive inhibitor due to the changes in the enzyme-substrate complex equilibrium [ 61 ].…”
Section: Discussionsupporting
confidence: 90%
“…The above-mentioned study has concluded that in the propoxur-resistant strain there was a decrease in the affinity of the enzyme to insecticides and substrate, as well as a decrease in the catalytic efficiency of AChE against the specific substrate (ATC). Similar results were obtained in other studies, where authors investigated AChE in OPs-and carbamateresistant insects [41][42][43]. We evaluated the kinetic parameters of AChE in the chlorfenapyrresistant M. domestica strain for the first time.…”
Section: Resultssupporting
confidence: 72%
“…The insecticide resistance associated gene, Ldace1 (Fournier et al ., 1992 ; Zhu & Gao, 1999 ; Clark et al ., 2001 ), was upregulated under the highest concentration of fluazinam, suggesting that this chemical can act similarly like insecticides as high expression levels of Ldace1 have been previously associated with the resistance against organophosphate and carbamate insecticides in CPB (Revuelta et al ., 2011 ; Margus et al ., 2021 ). On the other hand, if fluazinam slows down the growth of the larvae (see Clements et al ., 2018a ) it is possible that this difference between treatments is generated by the developmental differences among larvae as Ldace1 expression goes down when the larvae grow (Revuelta et al ., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we used Glutathione synthetase ( Gs ) gene, which is known to be related to neonicotinoid resistance in CPB (Clements et al ., 2016 , 2017 ) and acetylcholine esterase1 gene ( Ldace1 ), with high expression levels associated with resistance against organophosphate and carbamate insecticides in CPB (Revuelta et al ., 2011 ; Margus et al . 2021 ). Finally, we measured the expression levels of a heat shock protein gene, Hsp70 , which is an early marker of stress associated with the respiration process and temperature shock (Lee et al ., 2012 ; Chen et al ., 2014 ; Wang et al ., 2018 ).…”
Section: Methodsmentioning
confidence: 99%